The importance of molecular characters when morphological variability hinders diagnosability: systematics of the moon jellyfish genus Aurelia (Cnidaria: Scyphozoa) - Lawley, J. W.; Gamero-Mora, E.; Maronna, M. M.; Chiaverano, L. M.; Stampar, S. N.; Hopcroft, R. R.; Collins, A. G.; Morandini, A. C. (PeerJ, 2021)
Cryptic species have been detected across Metazoa, and while no apparent morphological features distinguish them, it should not impede taxonomists from formal descriptions. We accepted this challenge for the jellyfish genus Aurelia, which has a long and confusing taxonomic history. We demonstrate that morphological variability in Aurelia medusae overlaps across very distant geographic localities. Even though some morphological features seem responsible for most of the variation, regional geographic patterns of dissimilarities are lacking. This is further emphasized by morphological differences found when comparing lab-cultured Aurelia coerulea medusae with the diagnostic features in its recent redescription. Previous studies have also highlighted the difficulties in distinguishing Aurelia polyps and ephyrae, and their morphological plasticity. Therefore, mostly based on genetic data, we recognize 28 species of Aurelia, of which seven were already described, 10 are formally described herein, four are resurrected and seven remain undescribed. We present diagnostic genetic characters for all species and designate type materials for newly described and some resurrected species. Recognizing moon jellyfish diversity with formal names is vital for conservation efforts and other studies. This work clarifies the practical implications of molecular genetic data as diagnostic characters, and sheds light on the patterns and processes that generate crypsis.